Dead after dark eaudiobook - Kenyon, Sherrilyn (Tantor Media, 2019)
"Shadow of the Moon" by Sherrilyn Kenyon: Angelia has fought her entire life to make herself strong. Now, with her patria under fire, she has to protect her people from Fury and his werewolf clan. Vowing to bring him to justice, Angelia sets out alone . . . until the hunter becomes the hunted, and the only way for her to survive is to trust the very wolf she's sworn to kill. "The Story of Son" by J. R. Ward: Claire Stroughton is a beautiful lawyer who would rather spend the night with a legal brief than the man of her dreams. Then a routine client meeting turns dangerous—and deeply sensual—when she is held captive by a gorgeous man with an unworldly hunger . . . "Beyond the Night" by Susan Squires: When Drew Carlowe returns home to win back a lost love, he is quick to dismiss rumors that his estate is haunted by a stunning young ghost . . . until one passionate encounter leaves him mystified—and aching for more. "Midnight Kiss Goodbye" by Dianna Love: Trey McCree possesses an insatiable desire for Sasha Armand—and supernatural powers that could endanger her life as a human. But when they team up to stop an evil warlord, Trey discovers that Sasha can do way more than drive men wild . . .